Risk factors of paclitaxel-induced peripheral neuropathy in patients with breast cancer: a prospective cohort study - Lixian, Sun; Xiaoqian, Yu; Luyan, Guo; Lizhi, Zhou; Rui, Du; Hongyue, Yao; Caijie, Zhao; Fenghui, Yuan (Frontiers in Oncology, 2024)
Objective: Chemotherapy-induced peripheral neuropathy (CIPN) is a common and severe adverse reaction in taxane-based chemotherapy. This study aimed to analyze the risk factors of peripheral neuropathy in patients with breast cancer receiving paclitaxel chemotherapy to provide a reference for the early prevention of CIPN. Methods: We included 350 patients with breast cancer who received chemotherapy for the first time at the Tangshan People's Hospital between August 2022 and June 2023 and were followed for at least 3 months after the end of chemotherapy. The incidence of CIPN in patients with breast cancer was calculated, and risk factors for CIPN were analyzed using logistic regression analysis. Results: The incidence rate of CIPN was 79.1%. Multifactor logistic regression analysis indicated that age ≥45 years (odds ratio [OR]=5.119, 95% confidence interval [CI]=1.395-18.780) and ≥60 years (OR=9.366, 95% CI=1.228-71.421), history of hypertension (OR=3.475, 95% CI=1.073-11.250), cumulative dose of chemotherapy drugs >900 mg (OR=4.842， 95% CI=1.961-5.946), vitamin D deficiency (OR=6.214，95% CI=2.308-16.729), abnormal alanine aminotransferase (OR=3.154, 95% CI=1.010-9.844), anemia before chemotherapy (OR=2.770, 95% CI=1.093-7.019), infusion duration of chemotherapy drugs >30 min (OR=3.673, 95% CI=1.414-9.539), body mass index ≥24 kg/m 2 (OR=8.139, 95% CI=1.157-57.240), mild depression (OR=4.546, 95% CI=1.358-15.223), and major depression (OR=4.455, 95% CI=1.237-16.037) increased the risk of CIPN. Having a regular caregiver (OR=0.223, 95% CI=0.087-0.573), high levels of physical activity (OR=0.071, 95% CI=0.008-0.647), and strong social support (OR=0.048, 95% CI=0.003-0.682) were protective factors against CIPN. Conclusion: Clinical attention should